PENERAPAN MODEL QUICK ON THE DRAW UNTUK MENINGKATKAN KARAKTER TANGGUNG JAWAB DAN HASIL BELAJAR SISWA - Sundari, Fitri; Hanifah, Nurdinah; Djuanda, Dadan (Jurnal Pena Ilmiah, 2019)
This research exists because of lack of responsibility and learning outcomes in IPS lesson. Therefore there needs to be improvement through the application of Quick On The Draw to improve the character of student's responsibility and learning outcomes. Research carried out was PTK, with the research subject being students of class IVB Panyingkiran III SDN, which amounted to 28 students. Results increase every cycle, with a target of 85% success in learning outcomes, 100% teacher performance, 85% student activity. Planning cycle I 97%, implementation of 59% student activity 64%, learning outcomes 43% complete. Planning cycle II 100%, implementation 84%, student activity 71%, learning outcomes 61% complete. While cycle III is 100% planning, 100% implementation, studentj activity 90%, 86% learning outcomes complete. So that can be concluded that Quick On The Draw model can increase responsibility of learning outcomes of class IV B Panyingkiran III SDN on IPS lesson-.